2008
DOI: 10.1029/2008gl033942
|View full text |Cite
|
Sign up to set email alerts
|

Air‐sea interaction between tropical cyclone Nari and Kuroshio

Abstract: [1] The air-sea interaction between tropical cyclone Nari (Sep/6 -16/2001) and Kuroshio is studied using satellite observations and an ocean model. Nari crossed the Kuroshio several times, which caused variations in typhoon intensity. Nari weakened when it was over the shelf north of Kuroshio where cooling took place due to mixing of the shallow thermocline. The cyclonic circulation penetrated much deeper for the slowly-moving storm, regardless of Nari's intensity. Near-inertial oscillations are simulated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 77 publications
(89 citation statements)
references
References 14 publications
3
86
0
Order By: Relevance
“…Moreover, in the SECS, the sediment trap-collected material (e.g., biogenic POC) is less likely to be affected by bottom-sediment re-suspension due to the fact that the bottom (off northeast Taiwan) is mainly composed of rock and coral materials. Even though an upwelling phenomenon (mainly below 150 m) off northeast Taiwan has been reported by Wu et al (2008a), the cold dome in the surface water on the shelf-break in the study area of the SECS has only been intermittently observed in summer (Chern et al 1990;Liu et al 1992;Gong et al 1995;Jan et al 2011).…”
Section: Introductionmentioning
confidence: 76%
“…Moreover, in the SECS, the sediment trap-collected material (e.g., biogenic POC) is less likely to be affected by bottom-sediment re-suspension due to the fact that the bottom (off northeast Taiwan) is mainly composed of rock and coral materials. Even though an upwelling phenomenon (mainly below 150 m) off northeast Taiwan has been reported by Wu et al (2008a), the cold dome in the surface water on the shelf-break in the study area of the SECS has only been intermittently observed in summer (Chern et al 1990;Liu et al 1992;Gong et al 1995;Jan et al 2011).…”
Section: Introductionmentioning
confidence: 76%
“…One important response is the decrease of SST due to the strong vertical mixing caused by the typhoon (Price et al, 1994). According to the SST observations from the satellite, SST usually decreases 2-5 • C due to the typhoon passing (Cione and Uhlhorn, 2003;D'Asaro et al, 2007;Wu et al, 2008;Jiang et al, 2009). Dare and McBride (2011) studied the response Figure 10.…”
Section: Typhoon Tembinmentioning
confidence: 99%
“…The Kuroshio intrudes across the shelf break northeast of Taiwan and then affects the circulation in the East China Sea [Chao, 1990]. It also plays a crucial role in air-sea interactions along its mainstream [Wu et al, 2008;Kwon et al, 2010]. Therefore, the study of the Kuroshio has not only regional but also basin wide importance.…”
Section: Introductionmentioning
confidence: 99%